2015
DOI: 10.1371/journal.pone.0128754
|View full text |Cite|
|
Sign up to set email alerts
|

Gastroenteritis Therapies in Developed Countries: Systematic Review and Meta-Analysis

Abstract: ContextGastroenteritis remains a leading cause of childhood morbidity.ObjectiveBecause prior reviews have focused on isolated symptoms and studies conducted in developing countries, this study focused on interventions commonly considered for use in developed countries. Intervention specific, patient-centered outcomes were selected.Data SourcesMEDLINE, EMBASE, the Cochrane Database of Systematic Reviews, trial registries, grey literature, and scientific meetings.Study SelectionRandomized controlled trials, cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 51 publications
2
47
0
7
Order By: Relevance
“…Most meta-analyses suggest a modest benefit of probiotics in reducing the duration of diarrhoea by ~1 day and up to 2 days for rotavirus-induced diarrhoea, although studies have been performed largely in middle-income and high-income countries 3 , and some studies did not report a clear benefit 150,151 . The mechanisms underlying this have been postulated to include the activation of antigen-presenting cells, a reduction in the levels of pro-inflammatory cytokines, the modulation of effector T cell and regulatory T cell immune responses, innate immune signalling (through interactions with several TLRs) and the promotion of enterocyte proliferation and/or migration 152 .…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Most meta-analyses suggest a modest benefit of probiotics in reducing the duration of diarrhoea by ~1 day and up to 2 days for rotavirus-induced diarrhoea, although studies have been performed largely in middle-income and high-income countries 3 , and some studies did not report a clear benefit 150,151 . The mechanisms underlying this have been postulated to include the activation of antigen-presenting cells, a reduction in the levels of pro-inflammatory cytokines, the modulation of effector T cell and regulatory T cell immune responses, innate immune signalling (through interactions with several TLRs) and the promotion of enterocyte proliferation and/or migration 152 .…”
Section: Managementmentioning
confidence: 99%
“…Recommendations for the use of anti-emetics (such as metoclopramide, dimenhydrinate and ondansetron) for children with rotavirus disease have progressed from ‘not recommended’ to ‘possibly recommended’ owing to their effects of reducing the number of vomiting episodes and reducing the need for intravenous rehydration and hospitalization 150,159 . Indeed, one dose of ondansetron reduces the likelihood of needing intravenous rehydration, although this can increase diarrhoea output.…”
Section: Managementmentioning
confidence: 99%
“…Cette diminution a été de 16,5 heures, soit 40 % de la durée d'hospitalisation en cas de RIV. Ces résultats sont en accord avec 2 [9,10] des 3 méta-analyses ayant comparé réhydratation orale/entérale et intraveineuse [9][10][11]. Les méta-analyses de Fonseca et al Dans notre étude, la diminution du temps d'hospitalisation n'a pas été observée chez les enfants nécessitant une hospitalisation secondaire dans un service d'hospitalisation conventionnelle.…”
Section: Discussionunclassified
“…In spite of the fact that there are numerous studies about probiotics as a treatment for infectious diarrhea, there are some unsolved problems related to the dysentery description, remission criteria, probiotic type, probiotic potent dose, study quality, and probiotic effectiveness evaluation [23]. Recent studies using different probiotics have shown variable effects and meta-analyses show uncertain results due to inequality of studies [2426]. This suggests that each probiotic has its unique efficacy, so each probiotic needs to be tested to assess its efficacy in specific conditions [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews recommend further studies of probiotics in an outpatient setting [24, 28]. There are some meta-analyses which have assessed the results of probiotics in the treatment of AGE.…”
Section: Discussionmentioning
confidence: 99%